Defect structure in nitrogen-rich amorphous silicon nitride films - Yan, Baojie; Dias Da Silva, J. H. [UNESP]; Taylor, P. C. (Elsevier, 1998)
Electron spin resonance and photoluminescence measurements were carried out on nitrogen-rich, hydrogenated amorphous silicon-nitride films. Paramagnetic Si dangling bonds (K0 centers) are found in as-deposited films only after UV illumination. High temperature post-deposition annealing, followed by UV illumination, creates ESR-active, two-fold coordinated nitrogen dangling bonds (N02 centers). These two types of spin center are normally observed at room temperature. An extra component appears on the ESR spectrum measured at low temperature (6 K) for the as-deposited samples after UV illumination, at which temperature the line of the K0 center is saturated by microwave power. This component is tentatively attributed to N02 centers that are partially saturated. The photoluminescence efficiency is significantly decreased by the high temperature annealing. © 1998 Elsevier Science B.V. All rights reserved.
Keywords: a-SiNx:H films; K center; N02 center